2022
DOI: 10.1007/s42452-022-05180-z
|View full text |Cite
|
Sign up to set email alerts
|

2D boron nitride incorporating homonuclear boron bonds: stabilized in neutral, anionic and cationic charge

Abstract: In this work, by means of molecular simulation, we propose two new armchair boron nitride (BN) nanosheets with homonuclear boron bonds with chemical compositions: B30N24H18 and B33N21H18 under the scheme of the density functional theory at the level HSEh1PBE/6–311 +  + g(d,p). The main characteristic that these nanosheets contain is that the homonuclear boron bonds are concentrated at the central zone and the periphery of the central hexagon (B3N3) of the nanosheets, forming pentagonal and triangular geometrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Negative charge concentration attracted various molecules and enhanced the drug sensing affinity. 34 It is well known that high quality 2D hBN have been successfully prepared by molecular beam epitaxy (MBE), chemical vapor deposition (CVD) and metal-organic chemical vapor deposition (MOCVD). 20,35 The electronic and magnetic properties of hBN can greatly be altered by transition metal atoms doping.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Negative charge concentration attracted various molecules and enhanced the drug sensing affinity. 34 It is well known that high quality 2D hBN have been successfully prepared by molecular beam epitaxy (MBE), chemical vapor deposition (CVD) and metal-organic chemical vapor deposition (MOCVD). 20,35 The electronic and magnetic properties of hBN can greatly be altered by transition metal atoms doping.…”
Section: Introductionmentioning
confidence: 99%
“…Negative charge concentration attracted various molecules and enhanced the drug sensing affinity. 34 …”
Section: Introductionmentioning
confidence: 99%
“…Adsorption desulfurization (ADS) is a cost-effective, mild reaction condition and green technique that has become one of the highly promising alternative methods for HDS. Studies have shown that some special nanomaterials can be utilized as excellent performance adsorbents due to their high specific surface area. , As an emerging class of two-dimensional materials with high specific surface area, high adsorption capacity, and excellent thermal stability, hexagonal boron nitride nanosheets (BNNSs) have potential applications in the field of the adsorption process. BNNSs are a class of two-dimensional materials with graphene-like structures that can form π complexation interactions with dibenzothiophene in the ADS process. , To improve the adsorption performance, doping atoms onto BNNSs is one of the effective strategies, which can change the electronic structure of BNNSs. In addition to heteroatom doping, ,, metal atom doping is another efficient way to enhance ADS performance. , Metals elements are responsible for the enhanced ADS performance as they can be regarded as adsorption sites to form strong sulfur-metal (S–M) coordination bonds.…”
Section: Introductionmentioning
confidence: 99%
“…The hBN nanosheet, a structural counterpart of graphene, has also drawn great interest because of its special characteristics and vital applications. 28–30 The 2D monolayer hBN sheet, for illustration, demonstrates excellent thermal stability and high electrical resistance. More precisely, the hBN sheet maintains its stability at temperatures up to 1000 K, whereas graphene-based materials maintain their stability up to 800 K. 31 Further theoretical research revealed that boron monovacancies have higher formation energy than nitrogen monovacancies.…”
Section: Introductionmentioning
confidence: 99%